Photoassisted Synthesis of Silver Nanoparticles Using Riceberry Rice Extract and Their Antibacterial Application - Pimsumon Jiamboonsri; Sompit Wanwong (Journal of Nanomaterials, 2021)
The green synthesis of silver nanoparticles (AgNPs) has been attractive in biomedical applications due to its nontoxic and eco-friendly approach. This study presents the facile, rapid, and cost-effective synthesis of AgNPs by photoassisted chemical reduction using Riceberry (RB) rice extract as a reducing agent. The effects of reaction parameters including photoirradiation, irradiation time, the volume ratio of silver nitrate (AgNO3) to RB extract, and pH condition on the AgNP formation were also investigated. The characterization of AgNPs was determined by UV–visible spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier-transform infrared (FT-IR) spectroscopy. For antibacterial application, the synthesized AgNPs were studied by disc diffusion method against Escherichia coli and Staphylococcus aureus. The results indicated that light irradiation was an important factor to accelerate the formation of AgNPs. The synthesis parameters including volume of RB extract and pH condition significantly affected the particle size and crystallinity of AgNPs. The volume ratio of AgNO3 to RB extract 1 : 12.5 at pH 2.5 under photoirradiation was the successful condition to form nanometer-sized crystalline particles (average particle size of 59.48 ± 0.37 nm ) within 30 min with a rate constant of 0.210 min–1. The FT-IR measurement also suggested that the phytochemical constituents in RB extract were served as reducing and stabilizing agents for the synthesis of AgNPs. Additionally, the obtained AgNPs from various conditions demonstrated the antibacterial activity against both strains. Therefore, this study proposes an effective integration technique to synthesize AgNPs within a short time for antibacterial application.
Keywords: Nanoparticles: synthesis and applications; Moringa oleifera research and applications; Laser-Ablation Synthesis of Nanoparticles